A Sensor-based Garbage Gas Detection System - Sanger, Junaidy B.; Sitanayah, Lanny; Ahmad, Imam (2021 IEEE 11th Annual Computing and Communication Workshop and Conference (CCWC), 2021)
Garbage poses threat to the environment and human health. Toxic gases may causes respiratory disorders and other health related problems. This research focuses on design and implementation of a sensor-based system to sense the existence of garbage gases, namely Methane (CH4), Hydrogen Sulfide (H 2 S), and Ammonia (NH 3 ). Our sensor device consists of an Arduino Uno, a NodeMCU ESP8266, MQ-136, MQ-137, and TGS-2611 sensors. We implement two programs - an Arduino program at the sensor device and a PHP program that runs at the web server. In the experiments, the three sensors give higher values when the air is contaminated with garbage gas. The average sensor values from every sensor in the clean air and contaminated air experiments are 0.0904 ppm and 44.696 ppm for the MQ-137 sensor, 0.0624 ppm and 9.1884 ppm for the MQ-136 sensor, and 8.6236 ppm and 368.8128 ppm for the TGS-2611 sensor.